Cultural Tourism Product Authenticity and Tourist Value Perception: Testing Wang’s Existential Authenticity Theory in World Heritage Destinations - Nasution, Solahuddin; Tarigan, Safrizal Fazli; Nasution, Alifa Azzahra; Dalimunthe, Femmy I. (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
Wang’s (1999) existential authenticity theory offers a richer conceptual framework than MacCannell’s objective authenticity in explaining how tourists reconstruct selfhood through cultural experience. This study tests that theory in the context of North Sumatra’s Toba Caldera UNESCO Global Geopark by examining relationships between cultural tourism product authenticity, tourist value perception, satisfaction, and post-visit behavioural intentions. PLS-SEM analysis of 412 tourist surveys confirms that existential authenticity directly influences perceived value (Î²=0.58, p<.001) and satisfaction (Î²=0.47, p<.001), substantially stronger than objective authenticity (Î²=0.32, p<.05). Cultural tourism product type (intangible vs. tangible heritage) significantly moderates this relationship.